ANALISIS KETERKAITAN LATAR BELAKANG KEHIDUPAN SPIRITUAL DALAM NOVEL TEMUKAN AKU DALAM ISTIKHARAHMU KARYA ADI RUSTANDI MENGGUNAKAN PENDEKATAN EKSPRESIF - Wahid, Surachman; Titin Nurhayatin; Rani Siti Fitriani (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
A novel is a depiction of daily life that is found in a specific sastra. The novel originated in Italian, was known as a novella in Jerman, and was then translated into English before traveling to Indonesia. Novels are also described as prose-based short stories. “Temukan Aku dalam Istikharahmu” a novel by Adi Rustandi, is the only sacred work published in 2014 by Jakarta, Zettu Cetakan. This book draws inspiration from Tokoh Rengganis, which is explained throughout the novel. The authors not only expresses his feelings, but also offers ideas and solutions to the current problem. The authors in the story of his life expresses his private spiritual guidance through a tokoh of a devout old man who depicts his spiritual life and connects him to his spiritual community with his god. This study is being conducted to understand the life at the bottom of the pyramid.